Priene, Türkei: Erfolgreicher Abschluss der Sicherungs- und Konsolidierungsarbeiten am römischen Thermengebäude - Hoffschildt, Andreas; Filges, Axel (e-Forschungsberichte des DAI, 2023)
During the campaign of 2015, the conservation works at the Roman baths – which started in 2014 – were completed. The large building is now in a stable state. Cleaning and qualifying the ruin’s environment provide visitors’ safety and help understanding the structure and its later modifications. Parts of some rooms are now accessible for the first time. Effectively, the three-month work was supervised by a mixed German-Turkish team of architects – a model which is recommended in Priene also for the next years restoration projects.